Preparation method of high-thermal-conductivity silicone rubber composite material
Patent Information
- Application Number
- CN202211249096.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-10-12
AI Technical Summary
现有高导热有机硅橡胶复合材料存在分散性和均匀性问题,刚性太高、脆性大,机械性能差,氟引入增加硫化难度和成本,且高温耐溶剂性差。
A silicone rubber composite material was prepared by mixing methyl vinyl silicone rubber, organosilicon copolymer, thermally conductive filler and photoinitiator, and then pre-curing with ultraviolet light and high temperature vulcanization. The carbon nanotubes and silicon carbide fibers were modified by thiol-ene click reaction to form a thermally conductive network, which improved dispersibility and interfacial interaction.
It improves the thermal conductivity, mechanical properties and high-temperature solvent resistance of silicone rubber composites, reduces brittleness and vulcanization difficulty, and enhances the toughness and thermal stability of the materials.
Abstract
Description
Technical Field
[0001] This invention relates to the field of silicone rubber technology, specifically to a method for preparing a high thermal conductivity organosilicon rubber composite material. Background Technology
[0002] The development of modern electronics industry has promoted the development of new polymer materials; and silicone rubber is one of the polymers widely used in microelectronic devices. Heat dissipation is one of the problems that needs to be solved in electronic products, making the heat dissipation and high-temperature stability of silicone rubber products a major research area.
[0003] Thermally conductive silicone rubber is a type of silicone rubber made by blending high-molecular-weight silicone with thermally conductive materials. It is widely used in the electronics, electrical appliances, and instrumentation industries, requiring both high elasticity and high-temperature stability while rapidly transferring heat from the internal components to alleviate concentrated overheating. Current technologies, due to the need to improve thermal conductivity, involve a large amount of filler. This leads to several problems: firstly, issues with dispersion and uniformity; secondly, excessive rigidity and brittleness resulting in poor mechanical properties such as tear strength; and thirdly, weak interfacial interaction between the filler and the polymer, leading to high thermal resistance. On the other hand, fluorine is typically introduced to increase solvent resistance. However, the introduction of fluorine increases vulcanization difficulty and production costs, reduces mechanical strength, and results in poor high-temperature solvent resistance, making it unsuitable for use in harsh environments.
[0004] In summary, solving the above problems and preparing a high thermal conductivity organosilicon rubber composite filler is of great significance. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing a high thermal conductivity organosilicon rubber composite material to solve the problems mentioned in the background art.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0007] A method for preparing a high thermal conductivity silicone rubber composite material includes the following steps:
[0008] Step 1: Protect from light, add methyl vinyl silicone rubber, organosilicon copolymer, thermally conductive filler, vulcanizing agent and photoinitiator to the mixer in sequence, mix evenly to obtain silicone rubber prepolymer;
[0009] Step 2: Pre-cur the silicone rubber prepolymer under ultraviolet light in an electric field environment, and then vulcanize it at high temperature on a flat vulcanizing machine to obtain the organosilicon rubber composite material.
[0010] In a more optimized manner, the raw materials of the silicone rubber prepolymer include the following components: by weight, 45-55 parts methyl vinyl silicone rubber, 12-15 parts organosilicon copolymer, 32-40 parts thermally conductive filler, 1.5-2 parts vulcanizing agent, and 0.5-1 part photoinitiator.
[0011] A more optimized method for preparing the organosilicon copolymer is as follows: under an inert gas atmosphere, (mercapto)propylmethylsiloxane-dimethylsiloxane copolymer is dispersed in n-hexane, 3,4-epoxy-1-butene and a photoinitiator are added and stirred until homogeneous, followed by ultraviolet light-induced reaction, and n-hexane is removed by evaporation to obtain organosilicon copolymer A; under an inert gas atmosphere, organosilicon copolymer A is dispersed in toluene, dimer acid and zinc acetate are added, and the reaction is carried out at 100-105°C for 3-4 hours, and toluene is removed by evaporation to obtain organosilicon copolymer.
[0012] More optimally, the mass ratio of (mercapto)propylmethylsiloxane-dimethylsiloxane, 3,4-epoxy-1-butene, and dimer acid is 10:(0.05-0.08):(0.2-0.3).
[0013] In a more optimized manner, the preparation method of the thermally conductive filler is as follows: (1) Cyanobenol and potassium carbonate are dispersed sequentially in DMF, the temperature is set to 110-120℃, 1-bromooctene is added, the reaction is carried out for 1-2 days, the mixture is poured into an ice-water bath to precipitate, recrystallized, and dried to obtain a modifier; (2) Carbon nanotubes are dispersed in ethanol, mercaptopropyltrimethoxysilane is added, the mixture is stirred for 12 hours, ammonium fluoride is added and stirred for 24 hours, the mixture is washed and dried to obtain modified carbon nanotubes; Silicon carbide fibers are dispersed in ethanol, vinyltrimethoxysilane is added, the mixture is stirred for 12 hours, ammonium fluoride is added and stirred for 24 hours, the mixture is washed and dried to obtain modified silicon carbide fibers; (3) Modified carbon nanotubes, modified silicon carbide fibers, modifier, and photoinitiator are dispersed sequentially in n-hexane, subjected to ultraviolet light click reaction, washed and dried to obtain a thermally conductive material.
[0014] Ideally, the mass ratio of modified carbon nanotubes, modified silicon carbide fibers, and modifier is 5:1:2.
[0015] In a more optimized manner, the mass ratio of carbon nanotubes to mercaptopropyltrimethoxysilane in the modified carbon nanotubes is 1:(1-1.2); and the mass ratio of silicon carbide fibers to vinyltrimethoxysilane in the modified silicon carbide fibers is 1:(1.2-1.4).
[0016] In a more optimized manner, during the UV pre-curing process, the UV light intensity is 200–220 mW / cm² in an alternating electric field environment of 10–15 Hz and 50–100 V. 2Curing is carried out under light for 3-5 minutes; during high-temperature vulcanization, the first vulcanization is carried out for 10 minutes at a temperature of 160-170℃ and a pressure of 5-10MPa, followed by a second vulcanization at 180-200℃ for 2-4 hours.
[0017] An optimized method for preparing a high thermal conductivity silicone rubber composite material yields a silicone rubber composite material.
[0018] In this technical solution, a cross-linked network is formed between an organosilicon copolymer and linear organosilicon rubber, improving toughness while maintaining the degree of cross-linking, thus effectively enhancing mechanical properties. By rationally preparing a thermally conductive filler, the dispersion uniformity is increased while improving the interfacial interaction with the matrix polymer, thereby effectively improving thermal conductivity. The high-temperature solvent resistance is improved through the synergistic effect of the thermally conductive filler and the organosilicon copolymer.
[0019] (1) In this scheme, the (mercapto)propylmethylsiloxane-dimethylsiloxane copolymer is first modified by grafting 3,4-epoxy-1-butene onto the copolymer via a click reaction of thiol and olefin to obtain an organosilicon copolymer A containing epoxy groups. Then, the reaction of the epoxy groups with carboxyl groups is used to react it with a dimer acid to form an organosilicon copolymer with good thermoplasticity. This copolymer can undergo transesterification, polymer chain slippage, and rearrangement during the subsequent preparation of organopolymer rubber composites, exhibiting good high-temperature viscoelasticity. Simultaneously, the introduced dimer acid, being a cross-linked chain, effectively enhances the network cross-linking of the organosilicon rubber composite, while the long-chain alkyl groups effectively improve its water resistance. The dynamic transesterification process also contributes to its good heat resistance and solvent resistance.
[0020] (2) The scheme also utilizes the thiol-ene click reaction to graft carbon nanotubes modified with mercaptosilane coupling agent, vinyl modified silicon carbide fiber, and a modifier containing carbon-carbon double bonds to obtain thermally conductive fillers in sequence.
[0021] Among them, the two silane coupling agents exhibit similar compatibility with the two main components of the silicone rubber material, effectively improving the dispersibility of the filler. Simultaneously, they can cross-link within the composite material through photocuring, reducing interfacial thermal resistance and improving thermal conductivity. Pre-grafting of carbon nanotubes and silicon carbide fibers forms a pipe-to-wire interconnected thermally conductive network, further enhancing thermal conductivity. Furthermore, this thermally conductive network effectively improves mechanical properties, inhibits solvent swelling, and synergistically enhances high-temperature solvent resistance in conjunction with the silicone copolymer.
[0022] The modifier is prepared by the substitution reaction of the liquid crystal monomer cyanobiphenol with 1-bromooctene. It is also grafted into the thermally conductive filler through the reaction of thiol-ene, so that the thermally conductive filler contains cyanobiphenol. Under the action of an electric field, it is induced to align along the direction of the electric field and dispersed in an orderly manner in the polymer matrix, thereby significantly improving the thermal conductivity.
[0023] (3) By using ultraviolet light, the thermally conductive filler is pre-cured and uniformly interwoven in the network. Then, through a primary and secondary vulcanization process, the curing stress is reduced, and the brittleness is reduced. Because the hardness of silicone rubber composites with high filler content is relatively high, the generated thermal stress can cause microcracks, which is not conducive to the heat transfer channel between the silicone rubber material and the connecting material. Detailed Implementation
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] In the following examples, the carbon nanotubes are from Aladdin, catalog number C1212152, with a diameter of 11 nm; the silicon carbide fibers are from Xi'an Qiyue Biotechnology Co., Ltd., with an aspect ratio of 20-150; the (mercapto)propylmethylsiloxane-dimethylsiloxane copolymer is from Myriel, catalog number GEL-SMS-042; the methyl vinyl silicone rubber is from Wuhan Kanos Technology Co., Ltd., catalog number 8598479; and the dimer acid is from Shanghai Xuanya Biotechnology Co., Ltd., catalog number XY31120.
[0026] The modifier was prepared as follows: 5g of cyanobiphenol and 8g of potassium carbonate were sequentially dispersed in 150mL of DMF. The temperature was set at 120℃, and 7g of 1-bromooctene was added. The reaction was allowed to proceed for 2 days. The mixture was then poured into an ice-water bath to precipitate, recrystallized in ethanol solvent, and dried to obtain the modifier. The process can be scaled up proportionally.
[0027] The modified carbon nanotubes were prepared as follows: 10g of carbon nanotubes were dispersed in 800mL of ethanol, 11g of mercaptopropyltrimethoxysilane was added, and the mixture was stirred for 12 hours. Then, 3g of ammonium fluoride was added and stirred for 24 hours. The mixture was washed and dried to obtain the modified carbon nanotubes. The process can be scaled up proportionally.
[0028] The modified silicon carbide fiber is prepared as follows: 10g of silicon carbide fiber is dispersed in 800mL of ethanol, 1.2g of vinyltrimethoxysilane is added, and the mixture is stirred for 12 hours. Ammonium fluoride is then added and stirred for 24 hours. The mixture is washed and dried to obtain the modified silicon carbide fiber. The process can be scaled up proportionally.
[0029] Example 1:
[0030] Material preparation: (1) Under a nitrogen atmosphere, 100g of (mercapto)propylmethylsiloxane-dimethylsiloxane copolymer was dispersed in 200mL of n-hexane, and 0.5g of 3,4-epoxy-1-butene and 0.1g of photoinitiator 1173 were added and stirred evenly. Under 365nm ultraviolet light, the intensity was set to 80mW / cm. 2 After 30 minutes of light exposure, the hexane was removed to obtain organosilicon copolymer A. Under a nitrogen atmosphere, the obtained organosilicon copolymer A was dispersed in 200 mL of toluene, 2 g of dimer acid and 0.1 g of zinc acetate were added, and the mixture was reacted at 105 °C for 4 hours. The toluene was then removed to obtain the organosilicon copolymer, which can be scaled up proportionally. (2) 10 g of modified carbon nanotubes, 2 g of modified silicon carbide fiber, 4 g of modifier and photoinitiator were dispersed in 60 mL of hexane in sequence. Under 365 nm ultraviolet light, the intensity was set to 80 mW / cm. 2 After 30 minutes of exposure to light, the material is washed and dried to obtain a thermally conductive material that can be scaled up proportionally.
[0031] Step 1: By weight, in the dark, add 45 parts of methyl vinyl silicone rubber, 15 parts of organosilicon copolymer, 40 parts of thermally conductive filler, 2 parts of 2,4-dichlorobenzoyl peroxide, and 0.5 parts of photoinitiator 1173 to a mixer in sequence and mix evenly to obtain silicone rubber prepolymer.
[0032] Step 2: Place the silicone rubber prepolymer in an alternating electric field of 15Hz and 100V under 365nm ultraviolet light with an intensity of 220mW / cm². 2 Curing was performed under light for 3 minutes; then, on a flat vulcanizing machine, it was vulcanized for 10 minutes at 170℃ and 5MPa, followed by a second vulcanization at 180℃ for 4 hours to obtain the silicone rubber composite material.
[0033] Example 2:
[0034] Material preparation: (1) Under a nitrogen atmosphere, 100g of (mercapto)propylmethylsiloxane-dimethylsiloxane copolymer was dispersed in 200mL of n-hexane, and 0.6g of 3,4-epoxy-1-butene and 0.1g of photoinitiator 1173 were added and stirred evenly. Under 365nm ultraviolet light, the intensity was set to 80mW / cm. 2After 30 minutes of light exposure, the hexane was removed to obtain organosilicon copolymer A. Under a nitrogen atmosphere, the obtained organosilicon copolymer A was dispersed in 200 mL of toluene, and 2.5 g of dimer acid and 0.1 g of zinc acetate were added. The mixture was reacted at 105 °C for 4 hours, and the toluene was removed to obtain the organosilicon copolymer, which can be scaled up proportionally. (2) 10 g of modified carbon nanotubes, 2 g of modified silicon carbide fiber, 4 g of modifier, and photoinitiator were dispersed in 60 mL of hexane. Under 365 nm ultraviolet light, the intensity was set to 80 mW / cm. 2 After 30 minutes of exposure to light, the material is washed and dried to obtain a thermally conductive material that can be scaled up proportionally.
[0035] Step 1: By weight, in the dark, add 52 parts of methyl vinyl silicone rubber, 14 parts of organosilicon copolymer, 34 parts of thermally conductive filler, 1.6 parts of 2,4-dichlorobenzoyl peroxide, and 0.8 parts of photoinitiator 1173 to a mixer in sequence and mix evenly to obtain silicone rubber prepolymer;
[0036] Step 2: Place the silicone rubber prepolymer in an alternating electric field of 12Hz and 80V, and set the intensity of ultraviolet light at 365nm to 215mW / cm². 2 Curing was performed under light for 3 minutes; then, on a flat vulcanizing machine, it was vulcanized for 10 minutes at 165℃ and 6MPa, followed by a second vulcanization at 200℃ for 3 hours to obtain the silicone rubber composite material.
[0037] Example 3:
[0038] Material preparation: (1) Under a nitrogen atmosphere, 100g of (mercapto)propylmethylsiloxane-dimethylsiloxane copolymer was dispersed in 200mL of n-hexane, and 0.8g of 3,4-epoxy-1-butene and 0.1g of photoinitiator 1173 were added and stirred evenly. Under 365nm ultraviolet light, the intensity was set to 80mW / cm. 2 After 30 minutes of light exposure, the hexane was removed to obtain organosilicon copolymer A. Under a nitrogen atmosphere, the obtained organosilicon copolymer A was dispersed in 200 mL of toluene, 3 g of dimer acid and 0.1 g of zinc acetate were added, and the mixture was reacted at 105 °C for 4 hours. The toluene was then removed to obtain the organosilicon copolymer, which can be scaled up proportionally. (2) 10 g of modified carbon nanotubes, 2 g of modified silicon carbide fiber, 4 g of modifier and photoinitiator were dispersed in 60 mL of hexane in sequence. Under 365 nm ultraviolet light, the intensity was set to 80 mW / cm. 2 After 30 minutes of exposure to light, the material is washed and dried to obtain a thermally conductive material that can be scaled up proportionally.
[0039] Step 1: By weight, in the dark, add 55 parts of methyl vinyl silicone rubber, 13 parts of organosilicon copolymer, 32 parts of thermally conductive filler, 2 parts of 2,4-dichlorobenzoyl peroxide, and 0.5 parts of photoinitiator 1173 to a mixer in sequence and mix evenly to obtain silicone rubber prepolymer.
[0040] Step 2: Place the silicone rubber prepolymer in an alternating electric field of 10Hz and 50V, and set the intensity of the ultraviolet light at 365nm to 200mW / cm. 2 Curing was performed under light for 5 minutes; then, on a flat vulcanizing machine, it was vulcanized for 10 minutes at 170℃ and 10MPa, followed by a second vulcanization at 200℃ for 3 hours to obtain the silicone rubber composite material.
[0041] Comparative Example 1: The organosilicon copolymer was replaced with (mercapto)propylmethylsiloxane-dimethylsiloxane copolymer, and the rest was the same as in Example 2.
[0042] Specifically: Step 1: By weight, in the dark, add 52 parts of methyl vinyl silicone rubber, 14 parts of (mercapto)propylmethylsiloxane-dimethylsiloxane copolymer, 34 parts of thermally conductive filler, 1.6 parts of 2,4-dichlorobenzoyl peroxide, and 0.8 parts of photoinitiator 1173 to a mixer in sequence and mix evenly to obtain silicone rubber prepolymer;
[0043] Step 2: The silicone rubber prepolymer is subjected to an alternating electric field of 12Hz and 80V, and ultraviolet light of 365nm with an intensity of 215mW / cm. 2 Curing was performed under light for 3 minutes; then, on a flat vulcanizing machine, it was vulcanized for 10 minutes at 165℃ and 6MPa, followed by a second vulcanization at 200℃ for 3 hours to obtain the silicone rubber composite material.
[0044] Comparative Example 2: No organosilicon copolymer was introduced; all other aspects were the same as in Example 2.
[0045] Specifically: Step 1: By weight, in the dark, add 66 parts of methyl vinyl silicone rubber, 34 parts of thermally conductive filler, 1.6 parts of 2,4-dichlorobenzoyl peroxide, and 0.8 parts of photoinitiator 1173 to a mixer in sequence and mix evenly to obtain silicone rubber prepolymer;
[0046] Step 2: The silicone rubber prepolymer is subjected to an alternating electric field of 12Hz and 80V, and ultraviolet light of 365nm with an intensity of 215mW / cm. 2 Curing was performed under light for 3 minutes; then, on a flat vulcanizing machine, it was vulcanized for 10 minutes at 165℃ and 6MPa, followed by a second vulcanization at 200℃ for 3 hours to obtain the silicone rubber composite material.
[0047] Comparative Example 3: The amount of organosilicon copolymer introduced was increased to 25 parts, and the rest was the same as in Example 2;
[0048] Specifically: Step 1: By weight, in the dark, add 41 parts of methyl vinyl silicone rubber, 25 parts of organosilicon copolymer, 34 parts of thermally conductive filler, 1.6 parts of 2,4-dichlorobenzoyl peroxide, and 0.8 parts of photoinitiator 1173 to a mixer in sequence and mix evenly to obtain silicone rubber prepolymer;
[0049] Step 2: The silicone rubber prepolymer is subjected to an alternating electric field of 12Hz and 80V, and ultraviolet light of 365nm with an intensity of 215mW / cm. 2 Curing was performed under light for 3 minutes; then, on a flat vulcanizing machine, it was vulcanized for 10 minutes at 165℃ and 6MPa, followed by a second vulcanization at 200℃ for 3 hours to obtain the silicone rubber composite material.
[0050] Comparative Example 4: The mass ratio of modified carbon nanotubes, modified silicon carbide fibers, and modifier was changed to 3:3:2, and the rest was the same as in Example 2.
[0051] Comparative Example 5: No alternating electric field is set, and the rest is the same as Example 2.
[0052] Step 1: By weight, in the dark, add 52 parts of methyl vinyl silicone rubber, 14 parts of organosilicon copolymer, 34 parts of thermally conductive filler, 1.6 parts of 2,4-dichlorobenzoyl peroxide, and 0.8 parts of photoinitiator 1173 to a mixer in sequence and mix evenly to obtain silicone rubber prepolymer;
[0053] Step 2: Set the silicone rubber prepolymer to an intensity of 215 mW / cm under 365 nm ultraviolet light. 2 Curing was performed under light for 3 minutes; then, on a flat vulcanizing machine, it was vulcanized for 10 minutes at 165℃ and 6MPa, followed by a second vulcanization at 200℃ for 3 hours to obtain the silicone rubber composite material.
[0054] Experiment: The high thermal conductivity silicone rubber composites prepared in Examples 1-3 and Comparative Examples 1-5 were characterized. High-temperature solvent resistance was tested by immersion in diphenyl ether at 140°C for 6 hours. The expanded samples were then vacuum-dried, and the expansion rate was measured. The results are shown in the table below:
[0055] Example Tear strength (KN / m) <![CDATA[Thermal conductivity W / m . k]]> Expansion rate % Example 1 19.8 2.54 3.18 Example 2 20.3 2.58 3.24 Example 3 19.5 2.53 3.17 Comparative Example 1 18.0 2.42 5.21 Comparative Example 2 17.3 2.30 7.68 Comparative Example 3 18.6 2.48 3.15 Comparative Example 4 19.3 2.31 3.06 Comparative Example 5 20.5 2.18 3.08
[0056] Conclusion: The data in the table above show that the resulting silicone rubber composite material possesses excellent mechanical properties, thermal conductivity, and high-temperature solvent resistance. Comparing the data from Comparative Examples 1-5 with Example 2 reveals the following: In Comparative Example 1, the mechanical properties and high-temperature solvent resistance decreased because the silicone copolymer was replaced with (mercapto)propylmethylsiloxane-dimethylsiloxane copolymer; in Comparative Example 2, all properties significantly decreased due to the absence of silicone copolymer. In Comparative Example 3, the mechanical properties decreased due to excessive introduction of silicone copolymer. In Comparative Example 4, the thermal conductivity and expansion coefficient decreased significantly due to changes in the proportion of thermally conductive filler and the increase in silicon carbide fiber; in Comparative Example 5, the thermal conductivity decreased significantly due to the absence of an electric field.
[0057] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0058] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a high thermal conductivity organosilicon rubber composite material, characterized in that: Includes the following steps: Step 1: By weight, in the dark, add 45-55 parts of methyl vinyl silicone rubber, 13-15 parts of organosilicon copolymer, 32-40 parts of thermally conductive filler, 1.5-2 parts of vulcanizing agent, and 0.5-1 parts of photoinitiator into a mixer in sequence, mix evenly, and obtain silicone rubber prepolymer; Step 2: Place the silicone rubber prepolymer in an alternating electric field of 10–15 Hz and 50–100 V, with an ultraviolet light intensity of 200–220 mW / cm². 2 After curing under light for 3-5 minutes, vulcanize for 10 minutes on a flat vulcanizing machine at a temperature of 160-170℃ and a pressure of 5-10MPa, and then vulcanize for 2-4 hours at 180-200℃ to obtain the silicone rubber composite material. The preparation method of the organosilicon copolymer is as follows: under inert gas, (mercapto)propylmethylsiloxane-dimethylsiloxane copolymer is dispersed in n-hexane, 3,4-epoxy-1-butene and photoinitiator are added and stirred evenly, and ultraviolet light is used for click reaction. After evaporation of n-hexane, organosilicon copolymer A is obtained; under inert gas, organosilicon copolymer A is dispersed in toluene, dimer acid and zinc acetate are added, and the reaction is carried out at 100-105℃ for 3-4 hours. After evaporation of toluene, organosilicon copolymer is obtained. The preparation method of the thermally conductive filler is as follows: (1) Cyanobenol and potassium carbonate are dispersed in DMF in sequence, the temperature is set to 110-120℃, 1-bromooctene is added, the reaction is carried out for 1-2 days, the mixture is poured into an ice-water bath to precipitate, recrystallized, and dried to obtain the modifier; (2) Carbon nanotubes are dispersed in ethanol, mercaptopropyltrimethoxysilane is added, the mixture is stirred for 12 hours, ammonium fluoride is added and stirred for 24 hours, the mixture is washed and dried to obtain the modified carbon nanotubes; Silicon carbide fibers were dispersed in ethanol, vinyltrimethoxysilane was added, and the mixture was stirred for 12 hours. Ammonium fluoride was added and stirred for 24 hours. The mixture was then washed and dried to obtain modified silicon carbide fibers. (3) Modified carbon nanotubes, modified silicon carbide fibers, modifiers and photoinitiators are sequentially dispersed in n-hexane, subjected to ultraviolet light click reaction, washed and dried to obtain a thermally conductive material, wherein the mass ratio of modified carbon nanotubes, modified silicon carbide fibers and modifiers is 5:1:
2.
2. The method for preparing a high thermal conductivity organosilicon rubber composite material according to claim 1, characterized in that: The mass ratio of (mercapto)propylmethylsiloxane-dimethylsiloxane, 3,4-epoxy-1-butene, and dimer acid is 10:(0.05~0.08):(0.2~0.3).
3. The method for preparing a high thermal conductivity organosilicon rubber composite material according to claim 1, characterized in that: In the modified carbon nanotubes, the mass ratio of carbon nanotubes to mercaptopropyltrimethoxysilane is 1:(1-1.2); in the modified silicon carbide fibers, the mass ratio of silicon carbide fibers to vinyltrimethoxysilane is 1:(1.2-1.4).
4. The silicone rubber composite material prepared by the preparation method of the high thermal conductivity silicone rubber composite material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Methods for preparing modified vinyl silicone resin and organosilicone sealing compound containing modified vinyl silicone resin
CN105860083A
Dimer acid-modified polysiloxane coating and preparation method thereof
CN107298941A
